Carbonyl-Photoredox/Metal Dual Catalysis: Applications in Organic Synthesis - Zhu, Da-Liang; Young, David James; Li, Hong-Xi (Synthesis, 2020)
Photoredox/metal dual catalysis is a versatile tandem methodology to construct carbon–carbon and carbon–heteroatom bonds. The focus of this short review is the application of this technology to C(sp3)–C(sp3), C(sp3)–C(sp2), C(sp2)–C(sp2), C(sp2)–O, and C(sp3)–O bond formation induced by readily available and inexpensive carbonyl complexes as single electron transfer agents, photosensitizers, or hydrogen atom transfer agents.1 Introduction2 Homocoupling of Aryl Halides3 Functionalization of C(sp3)–H Bonds3.1 Dehydrogenation of Alkanes3.2 Arylation/Alkylation3.3 Carboxylation3.4 Acylation3.5 Hydroalkylation of Olefins3.6 Hydroalkylation of Imines4 Benzoylation of Aryl Bromides5 Aryl Esterification6 Oxidation of β-Keto Esters7 Conclusions and Future Outlook
Keywords: dual catalysis; carbonyl-photocatalysis; transition-metal catalysis; C–C bond; C–O bond